Proyecto de factibilidad de una casa de Té-Pastelería, en la ciudad de Quito, especializada en las ventas de cheesecakes e infusiones frías y calientes, endulzadas naturalmente - Vinueza Unda, Johanna Lizette (2015)
This project involves the creation of a Tea House named Siguiendo la Luna, whose purpose is the production and sale of two major products that are infusions and cheesecakes. Infusions can be local and imported and can be served hot or cold. Also it will be offered a widespread variety of cheesecakes, exotic flavors or fruit of the season, also chocolate and wafers. In addition, dishes of salt like sandwiches and salads will be offered so that the clients have more alternatives on the menu. Siguiendo la Luna also will offer also a quiet and cozy atmosphere, so customers can share with friends or colleagues a time pleasant and relaxing. It is for this reason that it is handled a slogan anti stress, which consists of having lockers at the entrance so that customers leave their belongings, especially their mobile devices in order to be disconnected from the world while their senses fall for the scents and flavors of infusions and cheesecake pastry. On the other hand, we will have supported by a highly trained staff in the management and service of food and beverages, is why that is probable to exceed the expectations of the customer in every way, which will lead to an increase in demand for the products. All in all, this project is presented in order to solve the shortage of this business concept in the north -central area of Quito city. Although existing business in town with this approach, you do not have greater choice of desserts.